Discrete mathematical modeling of biological phenomena: Case of drug concentration in the organism - Costa , Rian de Carvalho da; Araújo, Adriel silva; Lopes, Natália Brito; Silva, Ismael de Carvalho; Santos, Stefany Maria Silva; Araújo, José Fernando Silva; Silva, Lara Eduarda Monteiro; Linhares, Thiago Luan Santos; Carvalho, André Luís Moraes de; Cardozo, Francisco Das Chagas Silva (Seven Editora, 2023)
At first, mathematical modeling is a tool used to understand the occurrence of phenomena, and through the existence of a pattern in the recurrences, it is possible to formulate a recurrence expression where the phenomenon is modeled in such a way, understanding its behavior and predicting certain situations. In the study of biological phenomena, there is a need to understand a certain action in such a way, thus, to understand the process is given by Mathematical Modeling applying the equations of differences, in this way resulting in linear or non-linear functions, because of this modeling with N applications in the biological field, the study of the research project at UFDPar will be discussed as an example. DOI:https://doi.org/10.56238/devopinterscie-237